2008
DOI: 10.1128/aem.01133-07
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface Microbial Diversity in Deep-Granitic-Fracture Water in Colorado

Abstract: A microbial community analysis using 16S rRNA gene sequencing was performed on borehole water and a granite rock core from Henderson Mine, a >1,000-meter-deep molybdenum mine near Empire, CO. Chemical analysis of borehole water at two separate depths (1,044 m and 1,004 m below the mine entrance) suggests that a sharp chemical gradient exists, likely from the mixing of two distinct subsurface fluids, one metal rich and one relatively dilute; this has created unique niches for microorganisms. The microbial commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(140 citation statements)
references
References 62 publications
6
130
2
2
Order By: Relevance
“…South Africa gold mine euryarchaeotic group 1 was detected at 200-1000 m and at 1300-1500 m. At 1900 and 2300 m, over 99% of the sequences were classified to Methanobacteriaceae family, causing a reduction in community evenness, diversity and richness (Supplementary Table S4). The prevalence of Proteobacteria, Firmicutes and methanogenic archaea in Outokumpu was consistent with the detection of these taxa in geographically distant continental crustal areas (Gihring et al, 2006;Sahl et al, 2008).…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…South Africa gold mine euryarchaeotic group 1 was detected at 200-1000 m and at 1300-1500 m. At 1900 and 2300 m, over 99% of the sequences were classified to Methanobacteriaceae family, causing a reduction in community evenness, diversity and richness (Supplementary Table S4). The prevalence of Proteobacteria, Firmicutes and methanogenic archaea in Outokumpu was consistent with the detection of these taxa in geographically distant continental crustal areas (Gihring et al, 2006;Sahl et al, 2008).…”
Section: Resultssupporting
confidence: 51%
“…Previous studies using 16S rRNA gene cloning have reported up to 42 bacterial OTUs in continental crystalline rocks (Gihring et al, 2006;Sahl et al, 2008;Onstott et al, 2009), whereas analysis of rarefied pyrotag data obtained from Outokumpu in this study inferred 48-110 bacterial OTUs per sample (Supplementary Table S4). Archaeal OTU richness also greatly exceeded expectations based on earlier studies, with up to 112 OTUs detected in samples recovered above 1500 m (Takai et al, 2001;Sahl et al, 2008). Bacterial OTU richness peaked at 1300 m depth, which coincides with ophiolitic sequence of altered ultramafic rocks (that is, serpentinite, skarn and quartz).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Similar observations have been previously reported in other deep microbial ecosystems (Fry et al 1997;Sahl et al 2008). Basso and colleagues (2009) analyzed a deep subsurface gas storage aquifer and observed a microbial community primarily comprising Firmicutes and Deltaproteobacteria.…”
Section: Drill Mud Contamination Controlsupporting
confidence: 80%
“…Sequences belonging to the classes Alpha-and Gammaproteobacteria rarely occurred at this site (<3 %). Overall, sequences of this core were closely related to ubiquitous microorganisms previously recovered from marine or terrestrial environments contaminated with heavy metals (Selenska-Pobell et al, 2001;Akob et al, 2007;Bruun et al, 2010;Kampe et al, 2010), from soil (Phuong et al, 2008;Schouten et al, 2010), water, groundwater (Sahl et al, 2008) and petroleum crude oil samples (Yamane et al, 2008). Bacterial communities of the Ligurian Sea core KESC9-30 were composed of Proteobacteria (classes Alpha-, Beta-and Gammaproteobacteria), Chloroflexi, Bacteroidetes and candidate division OP8.…”
Section: Bacterial Communitiesmentioning
confidence: 99%